Effects of Labor Support Program on Pain-Coping Behavior and Childbirth Experience among Primiparous Women Who Received Oxytocin - ศิลธรรมกิจ ชนกพร; แสงอินทร์ ศิริวรรณ; ศุภศรี พิริยา (Journal of The Royal Thai Army Nurses, 2019)
This quasi-experimental research aims to examine the labor support program on pain-coping behavior and childbirth experience among primiparous women who received oxytocin. Sample were 50 primiparous women who received oxytocin and attended at delivery room, Samudprakan Hospital. Purposive sampling was used to recruit sample. They were divided into an experimental group (n = 25) and a control group (n = 25). The experimental group received labor support program and routine nursing care. The control group received routine nursing care. Research instruments used to collect the data composed of personal and obstetric information, pain-coping behavior observation form and the perception of childbirth experience questionnaire. The data were analyzed by using descriptive statistics and independent t-test. The findings revealed that the experimental group had significantly higher pain-coping behavior both cervical dilation 5-7 centimeter and 8-10 centimeter than the control group (t48 = 15.88, p < .001 and t48 = 24.50, p < .001, respectively) and had significantly higher childbirth experience than the control group (t48 = 22.7, p < .001). This study confirmed the effective of the labor support program could increase pain-coping behavior and childbirth experience. Therefore, hospitals should be used this program to care laboring women who received oxytocin.